Frontier : exploring the top ten emerging markets of tomorrow - Serkin, Gavin, 1971- (Bloomberg financial series., 2015)
Get ahead of emerging markets with top-performer picks for up-and-comers Frontierhelps investors successfully navigate markets that are yet to "emerge," with expert advice on spotting opportunities and minimising risks. With first-hand insights into frontier markets as we travel with big-name fund managers from Mark Mobius to Morgan Stanley, this practical guide ranks countries, stocks and bonds on a five- to ten-year horizon to steer investors toward the most promising destinations. Written in a compelling and accessible travelogue narrative, each chapter covers a specific country, providing invaluable market analysis and a deep understanding of the political, economic, and social background of those most likely to outperform. The key focus is on fresh ideas, based on the assessments from top performing money managers when meeting challenges, hostilities or adversity, and observations after interviewing high-level government officials and executives. With advanced economies shackled by debt and sluggish growth, investors are increasingly turning to emerging markets for better returns. Yet the money managers who came out on top in China, India, and Brazil are now focusing their attention on markets that have not yet emerged. This book applies the perspective of ten of the most successful fund managers in their field, providing an unparalleled guide to assessing investment potential in places better known for conflict, poverty and corruption. & middot; Discover which markets have the best prospects, and which are potential disasters & middot; Analyse individual markets by metrics including macro data, global relative value comparisons of stocks and bonds, buy/ sell triggers, and more & middot; Learn which industries, stocks and bonds should be considered in each market & middot; Examine each country through real-life on-the-ground assessment of corruption, conflict and other risks as well as inspirational breakthroughs that signal opportunities This is a practical manual for all investors - whether students or professionals - wanting to get to know the most promising new markets while avoiding the pitfalls. A must-read for corporate executives seeking global capital, Frontierprovides a better understanding of the changing international investment dynamic. Robin Wigglesworth, FT: "Invaluable." Mark Mobius, Templeton: "I love it! Beautiful descriptive writing." Aliko Dangote, Wealthiest African: "Captivating tales, masterly woven."